(untitled) (International Journal of Geoscience, Engineering and Technology, 2020)
In the present article a study is presented between the methods: analytical and numerical (Finite Difference Method “MDF”). In the analysis, the elastic line and bending moment of a beam were studied in both methods. The simply supported beam submitted to a distributed loading represents one of the most important examples in engineering. Deformation analysis is an important procedure in Structural Engineering. Initially, the Differential Equation of a beam is presented, and we tried to find the analytical and numerical solutions. Subsequently, the results are presented using tables and graphs for both methods and it was concluded that the numerical method provides satisfactory results.